Methodological quality and descriptive characteristics of prosthodontic‐related systematic reviews. (19th January 2013) - Aziz, T.; Compton, S.; Nassar, U.; Matthews, D.; Ansari, K.; Flores‐Mir, C.
Summary Ideally, healthcare systematic reviews (SRs) should be beneficial to practicing professionals in making evidence‐based clinical decisions. However, the conclusions drawn from SRs are directly related to the quality of the SR and of the included studies. The aim was to investigate the methodological quality and key descriptive characteristics of SRs published in prosthodontics. Methodological quality was analysed using the Assessment of Multiple Reviews (AMSTAR) tool. Several electronic resources (MEDLINE, EMBASE, Web of Science and American Dental Association's Evidence‐based Dentistry website) were searched. In total 106 SRs were located. Key descriptive characteristics and methodological quality features were gathered and assessed, and descriptive and inferential statistical testing performed. Most SRs in this sample originated from the European continent followed by North America. Two to five authors conducted most SRs; the majority was affiliated with academic institutions and had prior experience publishing SRs. The majority of SRs were published in specialty dentistry journals, with implant or implant‐related topics, the primary topics of interest for most. According to AMSTAR, most quality aspects were adequately fulfilled by less than half of the reviews. Publication bias and grey literature searches were the most poorly adhered components. Overall, the methodological quality of the prosthodontic‐related systematic was deemed limited. Future recommendations would include authors to have prior training in conducting SRs and for journals to include a universal checklist that should be adhered to address all key characteristics of an unbiased SR process.